The age of the flexi-farmer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Adapt! Adopt! Be adept! The exhortations of well, of those who exhort rain down every day on the heads of farmers. Out in the field, the flexibility of agricultural systems is not top of the agenda, but just how far should a farmer look ahead?Come...